Home a short history of an idea - Rybczynski, Witold (Penguin Books, 1987)
An architect discusses the idea of comfort and the Western cultural attitudes that have shaped it since the end of the Middle Ages, reviewing such cultural variables as intimacy and privacy, domesticity, ease, and ideas about light, air, and efficiency as they have changed over time, and making a plea for the primacy of cultural ideals as a basis for creating psychologically comfortable homes.